Growth and Flesh Quality of the Hybrid between Pangasianodon hypophthalmus and Pangasius bocourti - Hatachote, Sittichai; Sriphairoj, Kednapat; Na-Nakorn, Uthairat (Agriculture and Natural Resources, 2015)
A hybrid between the female striped catfish (Pangasianodon hypophthalmus) and the male Asian catfish (Pangasius bocourti) has been commercially produced with the expectation of being fast growing with white flesh, despite lacking scientific data on its commercial traits. This study compared the growth, carcass characteristics and nutritional values of the hybrid with those of the parental species. The fingerlings of the three genetic groups (average initial weight ranged from 13.62 to 23.32 g, P > 0.05) were randomly stocked in nine cages (13.5 m3 each), at a stocking density of 45 fish.m-3. They had been cultured for a period of 303 d (July 2009–May 2010). The results showed inferior growth and survival rate of the hybrid relative to the parental species (specific daily growth rates = 0.60 ± 0.24, 1.23 ± 0.02, and 1.20 ± 0.02%; survival rates = 37.83 ± 5.87%, 83.5 ± 3.82, and 95.93 ± 1.10%, for the hybrid, striped and Asian catfish, respectively, P < 0.05). Feed conversion ratios were not significantly different among the genetic groups (ranging between 1.26 ± 0.13 and 2.07 ± 0.71). The hybrid had the lowest dress-out (37.50%) and fillet percentage (32.15%) when compared with the parental species (P < 0.05). The flesh of the hybrid was identified as white based on color analysis. The firmness value was lowest in the hybrid. The hybrid had higher crude protein and ash and lower lipid contents than those of the parents.